ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR PESERTA DIDIK SAAT PANDEMI COVID-19 PADA MATA PELAJARAN IPS - Zulfitriani Zulfitriani; Aminuyati Aminuyati; Okianna Okianna (Universitas Tanjungpura, 2022)
This study aimed to determine the main factors causing students' learning difficulties and the teacher's efforts in overcoming the problems of students' learning difficulties during the COVID-19 pandemic in social studies subjects for class VII at SMP Negeri 03, Galing. The research method used was descriptive qualitative research. The informants were students of class VIIA and the teacher of social subjects. Data collection techniques used were observation, interviews, and documentation. The data collection tools were observation and interview guidelines, and documentation tools. The results of the study indicated: (1) the main factors causing students' learning difficulties can be observed from the aspects of internal and external factors. The internal factors can be observed from students' intelligence, attention, learning interest and motivation. While the external factors of students’ learning difficulties can be observed from the aspect of the school, which includes facilities, infrastructure, and their social environment, it can be concluded that the main factor was the aspect of attention. (2) the teacher's efforts in overcoming the problem of students' learning difficulties by finding out the learning problems faced by students, and the teacher's providing learning guidance, motivation, reprimanding students who do not focus on learning, and conducting remedial programs for students who do not reach the passing grade.